1987
DOI: 10.1038/328721a0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of immunization with a vaccinia-HIV env recombinant on HIV infection of chimpanzees

Abstract: Acquired immunodeficiency syndrome (AIDS) is caused by human immunodeficiency virus (HIV) and is now recognized as a worldwide epidemic for which there is no cure or vaccine. Chimpanzees are the only other animals that can be infected by HIV, and therefore the chimpanzee-HIV model system is useful for testing potential HIV vaccines. However, with one exception, there have been no reports of clinical manifestations of AIDS in chimpanzees. We report here results of an HIV vaccine trial in which nine chimpanzees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
54
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(54 citation statements)
references
References 0 publications
0
54
0
Order By: Relevance
“…These results suggest that recombinant poxviruses might prime for a similar secondary (anamnestic) neutralizing antibody response following virus infection. Hu et al showed that a recombinant vaccinia virus vector containing HIV-1 gp160 (strain LAV) primed for anamnestic neutralizing antibody production in chimpanzees following challenge with homologous virus (22). Although it is currently unknown whether an accelerated neutralizing antibody response would provide a clinical benefit in HIV-1-infected individuals, the fact that many months are needed for neutralizing antibodies to rise to detectable levels following initial infection (24,34,40,42) leaves open the possibility that it will.…”
mentioning
confidence: 99%
“…These results suggest that recombinant poxviruses might prime for a similar secondary (anamnestic) neutralizing antibody response following virus infection. Hu et al showed that a recombinant vaccinia virus vector containing HIV-1 gp160 (strain LAV) primed for anamnestic neutralizing antibody production in chimpanzees following challenge with homologous virus (22). Although it is currently unknown whether an accelerated neutralizing antibody response would provide a clinical benefit in HIV-1-infected individuals, the fact that many months are needed for neutralizing antibodies to rise to detectable levels following initial infection (24,34,40,42) leaves open the possibility that it will.…”
mentioning
confidence: 99%
“…Much of the effort to develop a vaccine for HIV infection has focused on the envelope glycoproteins. However, attempts to vaccinate chimpanzees with the entire molecule of gp 120 or with vaccinia virus recombinants bearing the HIV env protein did not elicit protection against subsequent virus challenge (Arthur et al, 1987 ;Hu et al, 1987;Berman et al, 1988). Furthermore, envelope proteins of HIV-1 were reported to have potential immunopathogenic features (Chanh et al, 1988;Chir-0000-9727 © 1991SGM mule et al, 1988Diamond et al, 1988;Weinhold et al, 1989); 'molecular mimicry' between segments of envelope proteins and domains of host proteins were also reported as a possible cause of autoimmune disorders in vivo (Weigent et al, 1986;Beretta et al, 1987;Golding et al, 1989): Therefore fragments of the virus that define critical epitopes for protective immunity, or structures that will mimic such epitopes, could be useful alternatives to existing systems as primer or stimulating immunogens.…”
Section: Introductionmentioning
confidence: 99%
“…Another may be the somewhat discouraging results from studies of vaccine preparations . [4][5][6][7][8][9] But the years of vaccine research may pay off after all. Reports in the summer of 1989 indicate that monkeys may be protected against simian immunodeficiency virus (SIV) by a whole killed preparation of the virus.…”
Section: Introductionmentioning
confidence: 99%